The impact of social participation on mental health among the older adult in China: an analysis based on the mental frailty index - Maiyu Jing; Qianqian Wang; Yuheng Jia; Xiaoyong Yu; Kan Tian (Frontiers in Public Health)
ObjectivesSocial participation and the psychological well-being of the older adult are correlated. A substantial body of research has delineated the relationship between social participation and the mental health of older adults, while the indicators for assessing the mental health of the older adult are not sufficiently systematic or comprehensive. This study aims to further explore the relationship between social participation and the mental health of older adults from the perspective of mental frailty, providing a reference for the improvement of health among the older adult population.MethodsWe selected 9,208 older adults aged 60 years and older from the China Health and Retirement Longitudinal Study (CHARLS) 2013–2018 database. The mental frailty index was constructed, which integrates both depression and cognitive status to assess the mental health status of the older adult. By using a fixed-effects model, we analyzed the impact of social participation on the mental health of the older adult and compared gender, residence and marriage difference. Meanwhile, the instrumental variables method was used to conduct endogeneity tests.ResultsOverall, 65.8% of the respondents had low social participation. Social participation had a significant enhancement effect on mental health in the older adult (β = −0.013, p < 0.001). In specific types of social participation, cultural and sports activities (β = −0.006, p < 0.001), communication and educational activities (β = −0.002, p < 0.05), and skill-enhancing (β = −0.006, p < 0.001) activities were negatively correlated with the index of mental frailty of the older adult, whereas volunteering activities (β = 0.002, p < 0.05) was positively correlated with the index of mental frailty of the older adult.ConclusionSocial participation has a positive effect on the mental health of the older adult in China, and the effect varies for the older adult with different characteristics, which suggests that social participation may be a protective factor for the mental health of the older adult population. Targeting differentiated population characteristics, individualized policies should be developed for different groups of older persons.